Computer simulation of the helix traveling-wave amplifier with harmonic signals - MacGregor, D.M. (IEEE electron device letters, 1980)
Both fundamental and second-harmonic output powers have been computed with an axially symmetric three-dimensional model of a helix traveling-wave amplifier. They agree reasonably well with measurements. For three beam power levels, the computed transfer curves show RF drive powers consistently about 3 dB below the measured powers and saturated output powers about 2 dB below the measured values. Inaccuracies in the assumed initial beam radius, density and velocity may have caused these differences. Suppressing the second harmonic raises the computed fundamental output power by 3 dB. The model accurately reproduces a measured 11 dB dip in the second harmonic as the fundamental signal saturates.